Vpliv okrova na hrup batnega kompresorja - Jerič, Anže (Strojniški vestnik, 2007)
The influence of the housing on the noise emitted by a typical reciprocating compressor for domestic appliances is analyzed. Sound-pressure and sound-intensity measurements were conducted to analyze the properties of the noise emitted by the compressor with and without the housing. The experimentally determined elastic properties of the compressor housing were compared with calculations based on a finite-element model. The results show that the dominant noise frequencies correspond to the eigen frequencies of the housing. Simple stiffening of the housing is shown to reduce the amplitude and modify the frequency content of the noise recorded outside the compressor.
Keywords: gospodinjski aparati; batni kompresorji; hrup; intenzivnost